Makna Kebahagiaan Pada Lansia Yang Bekerja Sebagai Pedagang Asongan - Pratama, Chandra Kurnia, Dr. Taufik, M.Si., Ph.D (2015)
The purpose of this research is to know, understand, and describe the meaning of happiness of the elderly who work as street vendors. Sampling was done by purposive sampling. The number of informants in this study five elderly with characteristics: working as hawkers, aged 60 years and above, are still able to communicate well, domiciled in Karisidenan Surakarta. This study uses qualitative methods of data collection using interviews and observations as supporting data, and analyzed descriptively. The results showed that the shape of the happiness of the elderly who work as street vendors include their happiness in carrying out its activities, by selling around the elderly can interact with the community and not feel bored with just sitting at home without any activities, earn maximum from the selling, and still rated health by God. While the factors that affect the happiness of the elderly who work as street vendors is their passion, patience and sincerity in the face of obstacles or barriers, support and suport of family, hope and confidence to continue selling at advanced age, and the presence self-actualization to still be working at advanced age and still able to give money to children and grandchildren. Keywords: happiness, Elderly working, peddler